The Bacterial Vaginosis among Pregnant Women in Jatinangor (Althea Medical Journal, 2020)
Background: Bacterial vaginosis (BV) is polymicrobial that causes superficial vaginitis due to a shift in vaginal flora. In pregnant women, BV can result in a significant risk of some serious consequences. The objective of this study was to identify the BV prevalence and to explore the characteristics and personal hygiene practices among pregnant women.Methods: This study was conducted in Desa Cipacing, Jatinangor, using the cross-sectional descriptive method, including pregnant women. The BV was detected by Gram-stained vaginal smears using Nugent Score. Furthermore, other microorganisms such as trichomoniasis and candidiasis were detected by direct microscopic observation. The questionnaire was distributed, consisting of details of personal hygiene practices.Results: In total, 17.9% of 52 pregnant women included were diagnosed with BV and 14.3% with mixed infection. Pregnant women with BV were predominantly aged younger than 25 years (61.1%), nullipara (50%) and in a second-trimester pregnancy (50%).Conclusions: Bacterial vaginosis (BV) is common among young pregnant women, predominantly in their first pregnancy. It is related to personal hygiene practices, indicating the need for targeted interventions of healthcare education among these young pregnant women to reduce the BV prevalence.
Keywords: Bacterial vaginosis; personal hygiene; pregnancy; vaginal discharge